2020
DOI: 10.1177/0883073820926634
|View full text |Cite
|
Sign up to set email alerts
|

Lacosamide-Induced Dyskinesia in Children With Intractable Epilepsy

Abstract: Lacosamide, an antiepileptic drug prescribed for children with refractory focal epilepsy, is generally well tolerated, with dose-dependent adverse effects. We describe 4 children who developed a movement disorder in conjunction with the initiation and/or uptitration of lacosamide. Three patients developed dyskinesias involving the face or upper extremity whereas the fourth had substantial worsening of chronic facial tics. The patients all had histories suggestive of opercular dysfunction: 3 had seizure semiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A recent case series has also demonstrated a dose-dependent relationship between lacosamide administration and dyskinesias of the face and/or upper extremity in children with histories suggestive of opercular dysfunction. 54 Two modern randomized controlled trials of fenfluramine in Dravet syndrome have been reported, though neither reports the incidence of treatment-emergent adverse events occurring in less than 10% of children. 55 , 56 Brivaracetam was approved for use in pediatric populations based on a randomized controlled trial including participants as young as 16 years and data showing similar pharmacologic properties in pediatrics as in adults.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case series has also demonstrated a dose-dependent relationship between lacosamide administration and dyskinesias of the face and/or upper extremity in children with histories suggestive of opercular dysfunction. 54 Two modern randomized controlled trials of fenfluramine in Dravet syndrome have been reported, though neither reports the incidence of treatment-emergent adverse events occurring in less than 10% of children. 55 , 56 Brivaracetam was approved for use in pediatric populations based on a randomized controlled trial including participants as young as 16 years and data showing similar pharmacologic properties in pediatrics as in adults.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 It has been shown to successfully terminate seizures in adults and children, with recent case studies demonstrating efficacy in neonates. 5,6 Its efficacy mixed with tolerable common side effects (occasional dizziness, somnolence, nausea and vomiting, headaches, diplopia, and dyskinesias) 3,7 has made it more popular in recent years. 8 Although many studies have found lacosamide to be a safe medication with mild side effects, 3,[8][9][10][11][12] there are also a handful of case studies that note significant cardiac events, most related to prolongation of the PR interval.…”
mentioning
confidence: 99%